A mortality study of electrical utility workers in Québec. Issue 1 (January 1996) - Baris, D; Armstrong, B G; Deadman, J; Thériault, G
Abstract : OBJECTIVES--The objective of this study was to investigate the mortality of electrical utility workers exposed to electric and magnetic fields. METHODS--A historical cohort mortality study was carried out on 21, 744 workers who were employed in an electrical company in the province of Québec between 1970 and 1988. The last job held by each study subject was coded. A job exposure matrix (JEM) was used to estimate the exposure to 60 Hz electric and magnetic fields, and pulsed electromagnetic fields (as recorded by the PEMF (POSITRON) meter) in this job. Standardised mortality ratios (SMRs) were calculated relative to Québec men. Because the exposure was exclusively among blue collar workers, the remainder of the analyses by exposure were restricted to them. Rate ratios (RRs) in the exposed groups relative to the background groups were estimated with Poisson regression. There were 1582 deaths by the end of follow up. RESULTS--SMRs were almost all below one and never substantially increased, although there were a few increased rate ratios (RRs). There was a significant RR of 2.00 (95% confidence interval (95% CI) 1.37-2.93) for deaths caused by accidents and violence in workers exposed to magnetic fields, RR of 1.82 (95% CI 1.25-2.65) for electric fields, and RR of 1.62 (95% CI 1.13-2.32) for pulsed electromagnetic fields. Occupational accidents related to power lines explain some of the excess of deaths from accidents and violence. Some association was found between magnetic fields and leukaemia, brain cancer, and suicide, between electric fields and brain cancer and suicide, and between pulsed electromagnetic fields and lung cancer, but these were not significant. CONCLUSION--These results are broadly reassuring that major causes of death are not strongly associated with exposure to electric and magnetic fields, but small numbers and approximate exposure assessments preclude the denial of any risk, in particular if it were to affect a rare cause of death.